Prehospital Surgical Airway Management: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Reardon, Robert F.; Robinson, Aaron E.; Kornas, Rebecca; Ho, Jeffrey D.; Anzalone, Brendan; Carlson, Jestin; Levy, Michael; Driver, Brian
Abstract: Bag-valve-mask ventilation and endotracheal intubation have been the mainstay of prehospital airway management for over four decades. Recently, supraglottic device use has risen due to various factors. The combination of bag-valve-mask ventilation, endotracheal intubation, and supraglottic devices allows for successful airway management in a majority of patients. However, there exists a small portion of patients who are unable to be intubated and cannot be adequately ventilated with either a facemask or a supraglottic airway. These patients require an emergent surgical airway. A surgical airway is an important component of all airway algorithms, and in some cases may be the only viable approach; therefore, it is imperative that EMS agencies that are credentialed to manage airways have the capability to perform surgical airways when appropriate. The National Association of Emergency Medical Services Physicians (NAEMSP) recommends the following for emergency medical services (EMS) agencies that provide advanced airway management. A surgical airway is reasonable in the prehospital setting when the airway cannot be secured by less invasive means. When indicated, a surgical airway should be performed without delay. A surgical airway is not a substitute for other airway management tools and techniques. It should not be the only rescue option available. Success of an open surgical approach using a scalpel is higher than that of percutaneous Seldinger techniques or needle-jet ventilation in the emergency setting.